Crude Oil Sludge Degradation in Microcosmic Scale: Simple Simulation as Preliminary Study on Land Treatment Bioremediation. - Nugroho, Astri (Makara Journal of Technology, 2006)
Crude Oil Sludge Degradation in Microcosmic Scale: Simple Simulation as Preliminary Study on Land Treatment Bioremediation. A study in microcosmic condition has been carried out to evaluate the bacterial hydrocarbonoclastic capability in increasing the oil sludge degradation being mixed with NPK fertilizer as nitrogen resources. Aerobic test was carried out by putting erlenmeyers in a shaker incubator, 120 rpm shaking speed, at 50°C temperature. While 150 days in microcosmic one observation showed that the consortium has the potential to grow up to 50% (v/v) sludge oil load. Maximum growth and maximum growth rate of the consortium occurred in the III C treatment (by adding 50% (v/v) sludge oil and by mixing nitrogen in the form of NPK fertilizer amounting 30% (w/v) of added substrat. The observation showed that at the day 150, all the treatments were degradated above 64%. Highest degradation accured in the III A treatment followed by the III C treatment amounting 88.72% and 87.19% respectively. The gas chromatography analysis showed that at t15 and t30, hydrocarbon C8 and C9 turned up and then vanished after t30. Hydrocarbon do increased at t30 while the relative abundance of C11 up to C17 was decreasing gradually. The biggest decreasing of that was in C14, as 85.28% before and 43.11% after. At the end of the study 7 species of bacteria were identified, 5 of them are of Bacillus sp, which are aerobical.